Biochar-based cement pastes and mortars with enhanced mechanical properties (Fracture and Structural Integrity, 2020)
Nowadays, the environmental impact of cementitious material industry and more generally of building activities is matter of concern, especially in terms of their effects on climate change and consumption of natural resources. Within this context, the aim of this paper is the investigation of the role of biochar, a solid carbonaceous by-product material resulting from biomass pyrolysis/gasification of residual biomass, as a sustainable ingredient for the production of cementitious materials, combining carbon sink properties with enhanced mechanical properties. Although biochar is mainly investigated as agricultural amendment, there is also evidence that biochar may be a eco-friendly material to enhance the sustainable performance of cementitious materials. As outlined in literature, biochar can be used as filler to modify the nanogranular nature of cement matrix, or as substitute of clinker to reduce the emissions of greenhouse gases related to cement production. In this work, biochar is added as micro-nano particles in different cementitious composites, i.e. cement pastes and mortars, as a function of filler or partial substitute of cement. The main mechanical properties of biochar-based materials are then investigated to determine the optimal percentage of biochar addition.
Keywords: Biochar; Nanoparticles; Cement-based composites; Strength; Toughness; Digital Image Correlation